Latihan Rebound Berbasis Permainan Meningkatkan Hasil Rebound Anak Usia 12-14 Tahun - Jovana Renaldy Gumay; Andri Prasetiyo; Resta Yolanda (Universitas Negeri Padang, 2026)
Background. Basketball plays an important role in physical, mental, and social development, especially during the rapid growth period of young people. Basketball, as a popular sport, demands technical skills, one of which is rebounding, which requires strength, coordination, and speed. Training methods using match rules are part of answering the hypothesis. Method. This study used an experimental method with a training effectiveness test, starting from a pre-test, then treatment, and finally a post-test. The research was conducted over 18 meetings over a period of 6 weeks. The subjects were 30 basketball athletes from Gading Rejo Academy in Pringsewu Regency with a total sampling of 40 using a purposive sampling method. The research instrument was a rebound skill test with a pre-test and post-test design. Results. showed a significant increase from an average of 8.7 rebounds in the pre-test to 18.5 rebounds in the post-test. The paired sample t-test obtained t = 12.47 > t = 2.045 with p = 0.000 < 0.05, which means the training model is effective in improving rebound skills. Conclussions. A game-based approach not only improves technical skills but also athletes' motivation and engagement, in line with the developmental characteristics of adolescence. Rebound training through play provides all children with the opportunity to develop their individual abilities.